Antibacterial Effect Of Ethanolic Extract Of Duku Seed (Lansium Domesticum) Against - M. Reza Eka Chandra; Shanty Chairani; Listia Eka Merdekawati (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Caries is a major oral health disease in Indonesia. Streptococcus mutans (S. mutans) is the main microorganism causes caries. Caries prevention can be done by mechanical or chemical methods. Plants can be used as an alternative for antibacterial chemical agent, one of which is duku seed. Ethanolic extract of duku seed showed the presence of alkaloids, flavonoids, saponins, and tannins that have antibacterial effect. Purpose: The purpose of this study was to evaluate the antibacterial effect of ethanolic extract of duku seed against S. mutans. Method: Present study was an in vitro laboratory study using post-test only control group design. Duku seed extracted by maceration with ethanol 96%. Antibacterial effect was carried out using microdilution method for MIC and MBC90 by ethanolic extract of duku seed with concentration of 0,19-100%. Inhibition zone was evaluated using disc diffusion method by ethanolic extract of duku seed with concentration of 1,56-12,5%, chlorhexidine gluconate 0,2% (positive control), and aquadest (negative control). Results were analyzed using one way ANOVA and Tukey’s LSD post-hoc. Result: The results showed that MIC and MBC90 were 0,19% and 3,12%, respectively. Ethanolic extract of duku seed at concentration of 3,12% showed the maximum inhibition zone of 4,50 mm, but still lower than chlorhexidine gluconate 0,2%. Conclusion: Ethanolic extract of duku seed has antibacterial effect against S. mutans, so it can be used as an alternative plant for dental caries prevention.